Chemical composition and structural changes of irrigated rice during storage - Kaminski, Tiago André; Brackmann, Auri; Silva, Leila Picolli da; Bender, Ana Betine Beutinger; Speroni, Caroline Sefrin (Semina: Ciências Agrárias, 2013)
The effect storage time at different temperatures (0.5, 20 and 35 °C) was periodically evaluated in regard to the chemical composition, elongation capacity and viscoamylographic properties of three irrigated rice varieties (BR-IRGA 410, IRGA 416 and IRGA 417) during 180 days. The alterations in the components of the polished grains were significant (P < 0.05) for the content of ash, phenolic compounds, amylose and resistant starch, with increments in the found values, mainly after longer periods and at higher storage temperatures. The experiment variables (irrigated rice variety, temperature and storage time) in the elongation parameters of the grains influenced significantly (P < 0.01), with expressive increases during the storage at 35 °C and the viscoamylographic properties, in other words, observed greater viscosity, resistance to breakdown and setback for the samples with higher content of amylose stored during storage at 35 °C. The alterations in the components of the grains, when significant (P < 0.05), were quite discreet and do not direct related to the significant alterations (P <0.01) in elongation and viscosity. The temperature turned out to be a variable of great influence in the rice ageing process, suggesting the possibility of storing this cereal in higher temperatures in order to provide culinary quality in a shorter period of storage.